Preoperative Hepatic Augmentation Versus Transarterial Chemoembolization for Hepatocellular Carcinoma With Insufficient Remnant Liver Volume: A Systematic Review and Meta‐Analysis - Wenjie Li; Hang Li; Qingyan Kong; Fei Teng; Zheyu Chen (Cancer Medicine)
ABSTRACT Background Increasing remnant liver volume before major liver resection is an effective measure to reduce postoperative adverse events of hepatocellular carcinoma (HCC). We aimed to provide evidence for optimal management of HCC patients with insufficient future remnant liver volume (FRLV). Methods A comprehensive search of various large medical databases, research registry platforms, and gray literature was performed up to May 2023. All comparative studies grouped by preoperative hepatic augmentation (PHA) and transarterial chemoembolization (TACE) were included. A random‐effects model was used for meta‐analysis, and the heterogeneity of the results was quantitatively assessed by funnel plots, sensitivity analyses, and subgroup analyses. Results A total of eight comparative studies were selected for inclusion in this analysis, including 3523 patients. 5‐year overall survival (hazard ratio [HR] = 1.52, 95% confidence intervals [CI] = 1.07–2.15) and disease‐free survival (HR = 1.72, 95% CI = 1.40–2.10) were significantly different between the PHA and TACE groups. There was no significant difference between PHA and TACE with respect to 90‐day mortality, postoperative complication rate, or serious complication rate (p > 0.05). In subgroup analysis, compared with portal vein embolization, associating liver partition and portal vein ligation was highly associated with longer survival and fewer recurrences (p < 0.05). None of the above results exhibited obvious bias or heterogeneity. Conclusions This study demonstrates that PHA allows for radical liver resection for HCC patients with insufficient FRLV without increasing the incidence of postoperative adverse events, which can effectively improve patient outcomes and delay tumor recurrence.